2012
DOI: 10.1371/journal.pone.0042246
|View full text |Cite
|
Sign up to set email alerts
|

p14ARF Post-Transcriptional Regulation of Nuclear Cyclin D1 in MCF-7 Breast Cancer Cells: Discrimination between a Good and Bad Prognosis?

Abstract: As part of a cell’s inherent protection against carcinogenesis, p14ARF is upregulated in response to hyperproliferative signalling to induce cell cycle arrest. This property makes p14ARF a leading candidate for cancer therapy. This study explores the consequences of reactivating p14ARF in breast cancer and the potential of targeting p14ARF in breast cancer treatment. Our results show that activation of the p14ARF-p53-p21-Rb pathway in the estrogen sensitive MCF-7 breast cancer cells induces many hallmarks of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 59 publications
5
24
0
Order By: Relevance
“…Downstream consequences of inhibiting DPP with Ala-BoroPro was evaluated by observing the effect on p21, a cell cycle regulator in MCF-7 cells (38), and the trypan blue exclusion cell proliferation assay (51). The Ala-BoroPro inhibitor had little or no effect on p21 protein expression in cell lines stably expressing the SK43 and SK51, whereas Ala-BoroPro increased SK51 expression under the same experimental conditions as shown by Western blot ( Figure 8A).…”
Section: Dpp2/4 Inhibitors Had No Overt Effect On Morphology and Cellmentioning
confidence: 87%
See 1 more Smart Citation
“…Downstream consequences of inhibiting DPP with Ala-BoroPro was evaluated by observing the effect on p21, a cell cycle regulator in MCF-7 cells (38), and the trypan blue exclusion cell proliferation assay (51). The Ala-BoroPro inhibitor had little or no effect on p21 protein expression in cell lines stably expressing the SK43 and SK51, whereas Ala-BoroPro increased SK51 expression under the same experimental conditions as shown by Western blot ( Figure 8A).…”
Section: Dpp2/4 Inhibitors Had No Overt Effect On Morphology and Cellmentioning
confidence: 87%
“…Cells were fixed and stained as described previously (38). FLAG antibody was used for SK1 detection, and Alexafluor 488 and 594 and Hoechst 33342 were used for visualization.…”
Section: Immunofluorescent Imagingmentioning
confidence: 99%
“…Our laboratory has demonstrated that activation of the p53-p21 pathway by p14ARF, in addition to rapid induction of cell cycle arrest, initiated a change in cellular metabolism consistent with a metabolically active senescence-like phenotype most likely to be important in cell survival and recurrence [16]. In our studies, the cancer cells maintained cell viability, and a sub-set of these cells retained the ability to proliferate [16, 17]. Dormant and senescent cells may be more resistant to cancer treatments so the more we understand about the behavior of these cells, the more likely we will be able to understand how cancers develop resistance to current treatments and, importantly, how they recur after treatment.…”
Section: Introductionmentioning
confidence: 80%
“…We have previously reported that activation of the p14ARF-p53 pathway in MCF-7 cells leads to cell cycle arrest, without inducing apoptosis, and, additionally, induces a metabolically active senescent-like phenotype [17]. To further explore the underlying mechanisms that lead to cell cycle arrest and metabolic/phenotypic changes we used SILAC LC-MS/MS methodology to determine the proteomic profile of MCF-7 cells post activation of p14ARF-p53 at 24 h and 72 h. Re-expression of p14ARF had no effect on the estrogen response in these cells (Fig 2 inset).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation